Clustered Cystic Changes in Long-Term Follow-Up Thin-Section Computed Tomographic Findings in Fibrotic Nonspecific Interstitial Pneumonia - Masanori Akira; Narufumi Suganuma (Canadian Respiratory Journal)
Objectives. The purpose of this study was to retrospectively assess cystic changes in findings on follow-up CT scans of patients with fibrotic nonspecific interstitial pneumonia (NSIP). Methods. The initial and last high-resolution CT scans of 58 patients with pathologically proven fibrotic NSIP were evaluated retrospectively. The median follow-up periods were 48 months (range, 12–183 months). The pattern, extent, and distribution of abnormal CT findings were compared with findings in the same region on previous and subsequent CT scans with a focus on cystic lesions. Results. Cystic lesions in a cluster were shown in 16 patients (28%) with fibrotic NSIP on the last CT scans. Focal clustered cysts were found in 5 cases and diffuse clustered cysts were seen in 11 cases. Focal clustered cysts mimicked honeycombing seen in usual interstitial pneumonia (UIP). Diffuse cysts were uniform in size in 7 of the 11 cases. Traction bronchiectasis in a cluster was seen in 3 of the 7 cases. The clustered cystic changes on CT during the course of NSIP mainly consisted of traction bronchiectasis and bronchiolectasis. Conclusions. Long-standing NSIP did not form honeycombing. The clustered cysts in patients with fibrotic NSIP were mainly remodeling of bronchiectasis.